Dancing like a toddler? The Green Climate Fund and REDD+ international rule‐making. Issue 2 (24th April 2019) - Recio, María Eugenia
Abstract : REDD+ is a mechanism developed under the United Nations Framework Convention on Climate Change (UNFCCC) to reduce deforestation and associated greenhouse gas emissions in developing countries. The UNFCCC has envisaged the Green Climate Fund (GCF) to play a key role in coordinating and supporting REDD+. With the GCF's foundations in place, this article reviews the GCF's role as a rule‐maker for REDD+. The analysis of GCF policies and their relationship with guidance from the UNFCCC Conference of the Parties (COP) reveals that the Fund has complemented, adjusted and further developed COP guidance with considerable autonomy. This is surprising in the light of the Fund's strong relationship with the UNFCCC, coupled with the fact that the same UNFCCC country parties are represented in the GCF's main decision‐making body. Such self‐directed regulatory activity may evince the GCF's intention to leave a long‐lasting impact in the fragmented financing landscape for REDD+ implementation.